Oxygen causes fetal pulmonary vasodilation through activation of a calcium-dependent potassium channel. - Cornfield, D N (1996)
At birth, pulmonary vasodilation occurs as air-breathing life begins. The mechanism of O2-induced pulmonary vasodilation is unknown. We proposed that O2 causes fetal pulmonary vasodilation through activation of a calcium-dependent potassium channel (KCa) via a cyclic nucleotide-dependent kinase. We tested this hypothesis in hemodynamic studies in acutely prepared fetal lambs and in patch-clamp studies on resistance fetal pulmonary artery smooth muscle cells. Fetal O2 tension (PaO2) was increased by ventilating the ewe with 100% O2, causing fetal total pulmonary resistance to decrease from 1.18 +/- 0.14 to 0.41 +/- 0.03 mmHg per ml per min. Tetraethylammonium and iberiotoxin, preferential KCa-channel inhibitors, attenuated O2-induced fetal pulmonary vasodilation, while glibenclamide, an ATP-sensitive K+-channel antagonist, had no effect. Treatment with either a guanylate cyclase antagonist (LY83583) or cyclic nucleotide-dependent kinase inhibitors (H-89 and KT 5823) significantly attenuated O2-induced fetal pulmonary vasodilation. Under hypoxic conditions (PaO2 = 25 mmHg), whole-cell K+-channel currents (Ik) were small and were inhibited by 1 mM tetraethylammonium or 100 nM charybdotoxin (CTX; a specific KCa-channel blocker). Normoxia (PaO2 = 120 mmHg) increased Ik by more than 300%, and this was reversed by 100 nM CTX. Nitric oxide also increased Ik. Resting membrane potential was -37.2 +/- 1.9 mV and cells depolarized on exposure to CTX, while hyperpolarizing in normoxia. We conclude that O2 causes fetal pulmonary vasodilation by stimulating a cyclic nucleotide-dependent kinase, resulting in KCa-channel activation, membrane hyperpolarization, and vasodilation.